Adsorption of nitrogen, methane, and carbon monoxide on aluminosilicate and aluminophosphate molecular sieves. - Predescu, Ligia. (University of Ottawa (Canada), 1996)
Considering the difficulties associated with the experimental determination of binary mixture adsorption isotherms, pure-gas adsorption information becomes vital in the prediction of these isotherms and the corresponding phase equilibria necessary in the design of adsorptive separation units. Experimental equilibrium isotherms describing the adsorption of pure N$\rm\sb2,\ CH\sb4,$ and CO in a natural aluminosilicate molecular sieve (clinoptilolite from Cuba) and two synthetic small-pore aluminophosphate molecular sieves (AlPO$\sb4$-17 and AlPO$\sb4$-18) have been determined using the volumetric method at 40$\sp\circ$C over a pressure range up to about 1000 mm Hg, and subsequently fitted with the Langmuir and Flory-Huggins Vacancy Solution Theory equations. Additional Langmuir and FH-VST fits of equilibrium isotherms previously measured over the same pressure range at room temperature and 40$\sp\circ$C to describe the equilibrium adsorption of the same three adsorbates in two aluminosilicate molecular sieves (natural clinoptilolite from Turkey and zeolite 5A), as well as in a medium-pore aluminophosphate molecular sieve AlPO$\sb4$-11 were also obtained. The Freundlich equation was found to yield a better fit than either the Langmuir or FH-VST equations for the experimental adsorption isotherms of N$\sb2$ and CO on AlPO$\sb4$-17. The higher observed capacities of the aluminosilicate molecular sieves, compared to the aluminophosphates, were attributed to the energetic heterogeneity conferred by the presence of framework-charge compensating cations. The model parameters obtained by fitting the experimental pure-component adsorption isotherms permitted the prediction of the mixture adsorption phase diagrams and the binary adsorption isotherms by the Extended Langmuir Model and the Flory-Huggins Vacancy Solution Model for the three possible binary mixtures at 101.3 kPa total pressure and the pure-component adsorption temperatures investigated. The Ideal Adsorbed Solution Theory was also applied with the explanation of the behaviour predicted by each model for each adsorption system was attempted. (Abstract shortened by UMI.)
Keywords: Engineering, Chemical.